FROM DIVINE COMMAND AND PROPHETIC GOALS TO SAPIENTIAL CHARACTER FORMATION: A SURVEY OF OLD TESTAMENT ETHICAL REFLECTION INFORMED BY PHILOSOPHICAL ETHICS - Bosman, Hendrik Ludolph (Scriptura, 2014)
At first attention will be given to recent surveys of the study of Old Testament ethical reflection. Then it will be argued that the study of ethics in general can provide a theoretical frame according to which different modes of ethical reflection can be discerned in the Old Testament:  A deontological ‘Divine command’ type of ethic rooted in the theophany on Mount Sinai through the communication of the Ten Commandments and the ‘mitzvot’.  A teleological or consequentialist type of ethic manifested in the prophetic emphasis on a covenantal relationship with God and other human beings.  A perfectionist or virtue ethic found in later wisdom and priestly literature that aspires to be wise and holy.  A descriptive ethic that focuses on the ‘is’ of Old Testament ethics then and not on the ‘ought’ of modern ethics now. In conclusion, it will be suggested that more attention should be given to the dialogue between the study of biblical ethics and the meta-theory undergirding philosophical ethics.